Red Ginger's Anti-Anxiety Effect on BALB/c Strain Mice (Mus musculus) Pro-Inflammatory and Anti-Inflammatory Measurements as Anxiety Model - Ira Aini Dania; Aldy Safruddin Rambe; Urip Harahap; Elmeida Effendy; Tuti Wahmurti; Syafruddin Ilyas; Muhammad Rusda; Mustafa Mahmud Amin (مجلة بغداد للعلوم, 2023)
There is a correlation between the occurrence of anxiety and the production of inflammatory mediators, and red ginger rhizome is a well-known herbal product with a high content of phenolic and flavonoid compounds that can be used as anti-inflammatories and antioxidants. The aim of study to evaluate the effect of red ginger as antianxiety in mice (Mus musculus) BALB/c strain by measuring levels of TNF-α, IL-6 and IL-10.  Anxiety model mice were carried out by giving treatment with the Forced Swimming Test (FST) for 7 days then assessed by carrying out the Elevated Plus Maze for Mice (EPM) test for one day. After the treatment, the anxiety mice model was made, followed by administration of red ginger ethanol extract therapy for 14 days. The distribution of the experimental animal model groups was divided into control groups (KN, K-, K+) and treatment groups (P, P2, P3).There was a significant difference the decreased of the TNF-α levels at the all of treatment groups with red ginger rhizome extract (P1, P2, P3) compared with the control groups (KN, K-) (p<0.05), the significantly decreased of IL-6 levels in the three doses treatment group (P1, P2, P3) compared to the control group (K-, K+) (p <0.05) and an increase in IL-10 levels in the 50 mg treatment group compared to group K -, statistically not significant (p>0.05).In overall, this study suggests that FST stimulation will create anxiety symptoms and behavior as well as impact cytokine levels, namely elevated levels of TNF-α and IL-6. Giving red ginger ethanol extract has the potential to be researched further for reducing anxiety symptoms because it can block pro-inflammatory cytokines by significantly decreased levels of TNF-α, IL-6, and increased IL-10 cytokines a brief abstract about your paper’s subject of study.